Le jeu du bâton, des pharaons à l’Unesco : patrimoine, identification et construction mémorielle dans le Ṣaʿīd égyptien - Séverine Gabry-Thienpont (Transposition)
Inscribed on the ICH list since 2016, taḥṭīb is an Egyptian practice typically performed at wedding celebrations and pilgrimages (mawlid). It is an exclusively male martial art with strict rules, in which two men, each armed with a stick, perform a combat in a choreographed series of defined figures. Music is central to taḥṭīb: the players are accompanied—encouraged and restrained—by the playing of mizmār and ṭabla baladi. Like many rural practices, taḥṭīb is considered by both its participants and spectators to be an ancestral tradition tracing back to Egypt’s Pharaonic era. After presenting the practice of taḥṭīb in twenty-first century Egypt, I will examine elements of the Pharaonist discourse, the resulting heritagisation processes, and the recent developments that led to Adel Boulad’s creation of Modern Tahtib. This analysis will focus on the memory constructions currently at play in Egypt, their reception abroad—in this case, in France—and how they allowed taḥṭīb and its music to be inscribed on the ICH list.